Epigenetic memory of epithelial–mesenchymal transition: linking transient plasticity to metastasis, therapy resistance, and immune evasion - Dominika Denisz; Magdalena Fabian; Jan Olszewski; Karolina Bajdak-Rusinek (Cellular Oncology, 2026)
Abstract Epithelial–mesenchymal transition (EMT) is increasingly recognized as a dynamic, plastic process that equips tumor cells with invasive capacity, stress tolerance, stem-like features, and adaptability, contributing to metastasis, therapeutic failure, and immune escape. Accumulating evidence indicates that these effects can outlast the inducing signal: tumor cells may retain molecular and functional traces of prior EMT exposure, biasing future cell-state behavior. This Review terms this phenomenon EMT memory. We propose EMT memory as a conceptual framework distinguishing it from EMT induction and maintenance through its persistence after signal withdrawal, its capacity to alter future cellular responsiveness, and, in its strongest form, its transmissibility across cell division. DNA methylation and chromatin-state remodeling emerge as the most plausible core substrates, reinforced by histone dynamics, chromatin remodelers, and noncoding RNA networks that stabilize post-EMT states. Temporal concepts including hysteresis, reversibility windows, and partial EMT stabilization clarify when transient plasticity becomes durably encoded, helping explain why highly aggressive tumor cells are often not fully mesenchymal yet remain strongly metastatic, drug tolerant, and immune evasive. We argue that metastatic competence, therapy resistance, and immune evasion can be viewed as functional outputs of remembered plasticity rather than solely as consequences of a contemporaneous mesenchymal phenotype. If transient EMT can be consolidated into persistent adaptive states, therapeutically relevant vulnerabilities may lie not only in EMT-inducing pathways, but also in the mechanisms that encode, reinforce, and preserve EMT memory—positioning memory-bearing states as an important target for future therapeutic strategies.